Wireless In Situ Catalytic Electron Signaling‐Mediated Transcriptomic Reprogramming for Neuron Regeneration via Adaptable Antennas - Hoi Man Iao; Chih‐Ying Chen; Ya‐Hui Lin; Wan‐Chi Pan; Chun‐Yi Liang; Hsiu‐Ching Liu; Lo‐Jei Ching; Pei‐Yu Weng; Min‐Ren Chiang; Ru‐Siou Hsu; Tsu‐Chin Chou; I‐Chi Lee; et al. (Advanced Science)
Abstract Electron signaling and oxygen level are vital for regulating neural‐cell fate and brain recovery. However, clinical challenges arise from the short half‐life and the difficulty of spatiotemporally controlled oxygen release and electric signals. In this study, a wireless‐charging sustained oxygen release from conductive microgels (SOCO) served as an antenna and an on‐demand O2 release for nerve regeneration is developed. Introducing “electromagnetic messenger”, using external alternating magnetic field (AMF) to enhance catalytic oxygen release and electrical stimulation to promote the reconstruction of blood vessels and neurons in vivo. SOCO also reduces TBI glial scarring by reducing activated microglia and stellate cells, promoting infiltration of new neurons. In whole‐brain analyses, effective somatostatin (Sst) production inhibits gamma‐aminobutyric acid (GABA) synthesis in injured areas, thereby improving brain function and behavioral recovery. Furthermore, spatial multiomics combined with single‐cell deconvolution analysis reveals the treatment reprogramming in vivo brain transcriptome of angiogenic markers (Il1a, Lgals3) and GABAergic pathway via modulation of GAD65/67 activity, guiding angiogenesis and neuronal regeneration. This in situ catalytic SOCO with noncontact AMF presents an “electromagnetic messenger”‐based therapeutics for reprogramming the neuro‐regeneration and brain function recovery in TBI.